Прогностичка вредност нивоа MVCD и MOP1 у серуму у процени прогнозе код пацијената са сепсом: Нивои серума MVCD и MOP1 у прогнози сепсе - Zhan, Xiaobo; Yang, Xue; Zeng, Xiaoqin; Zhou , Quancheng; Cheng, Xiaofan; Liao, Wei (Journal of Medical Biochemistry, 2026)
Objective To investigate the prognostic significance of serum levels of ‌Member of PAS protein 1 (MOP1) and Mammalian-derived Vascular Endothelial Growth Factor (MVCD) for the prognosis of children with sepsis in the pediatric intensive care unit (PICU). Methods We selected 124 pediatric patients with sepsis admitted to our hospital’s PICU from September 2023-September 2025 as Group B and another 100 pediatric patients admitted to the PICU during the same period without sepsis-related infections as Group A. Additionally, Pediatric patients with sepsis were split into two groups based on their prognosis after 28 days: a survival group (n = 80) and a mortality group (n = 44). The pediatric patients’ levels of MOP1 and MVCD were tested and compared after they were admitted. In pediatric patients with sepsis in the PICU, the predictive significance of serum MVCD and MOP1 was assessed using receiver operating characteristic (ROC) curves. To find out what characteristics affected the prognosis of pediatric sepsis patients in the PICU, multivariate logistic regression analysis was employed. Results Group B’s serum levels of MOP1 and MVCD were substantially higher than Group A’s. In comparison to the nonsurviving group, the surviving group’s serum levels of MVCD and MOP1 were noticeably lower. There were statistically significant differences between the groups (P<0.05). When assessing the prognosis of pediatric intensive care unit (PICU) sepsis patients, the ROC curve results showed that the sensitivity and specificity were 90.93% and 70.00%, respectively, and that the area under the curve for serum MVCD was 0.877, with a cutoff value of 146.87 ng/L. With a cutoff value of 35.53 ng/L, the area under the curve for serum MOP1 was 0.848 for assessing the prognosis of pediatric sepsis in the PICU. The sensitivity and specificity were 90.93% and 62.53%, respectively. In the assessment of the prognosis of pediatric intensive care unit sepsis, the sensitivity and specificity for MVCD+MOP1 were 86.39% and 62.53%, respectively, with an area under the curve of 0.926. A multivariate logistic regression analysis showed that serum levels of C-reactive protein [odds ratio (95% CI) = 2.436 (1.634–3.622)], MOP1 [odds ratio (95% CI) = 3.407 (1.880–6.144)], and MVCD [odds ratio (95% CI) = 3.782 (1.859–7.736)]acute physiology and chronic health evaluation score [odds ratio (95% confidence interval) = 3.212 (1.802–5.720)] and N-terminal pro-brain natriuretic peptide [odds ratio (95% confidence interval) = 3.037 (1.739–5.308)]. were risk factors influencing children with sepsis in the intensive care unit’s chance of dying (P < 0.05). Conclusion Children with sepsis in the PICU had higher expression levels of MVCD and MOP1 in their peripheral blood, and there is a strong correlation between these raised levels and the children’s prognosis. These findings have good clinical value for the prognostic evaluation of children with sepsis in the PICU.